A longitudinal study of the intra‐country variations in the provision of residential care for adult persons with an intellectual disability. (10th July 2012) - McConkey, R.; Kelly, F.; Craig, S.; Mannan, H.
Abstract: Background Small‐scale community accommodation is the preferred alternative internationally to the institutional and congregated services that previously dominated residential care for persons with intellectual disability. The strategies required for changing to new service models are not well researched. Method The National Intellectual Disability Database in Ireland provided the data to explore the changes in provision that occurred over a 10‐year period and the extent of the intra‐country variation across eight administrative areas for health services. Data were extracted for 2 years, 1999 and 2009, for over 7000 adult persons resident in either congregated or community‐based accommodation. Comparative indicators were calculated for the eight areas as well as nationally. In addition, over 4000 persons living in congregated settings were tracked over the 10 years to ascertain relocations as well as gathering information on the numbers of people newly admitted to each type of accommodation. Results Marked variations across the eight areas were found in the overall numbers of people in residential accommodation, the proportion of persons living in congregated settings and the extent of changes in the numbers of people in each type of accommodation. Moreover, fewer than 15% of people had relocated nationally from congregated settings over the 10‐year period and the number of new admissions to this form of provision remained high in certain areas. Conclusions The implementation of new forms of provision was not uniform across Ireland and possible reasons are proposed. Among the wider lessons internationally is the need for robust systems to monitor service provision nationally and locally if equity of access is to be achieved.